Short Course in International Intellectual Property Rights : Protecting Your Brands, Marks, Copyrights, Patents, Designs and Related Rights Worldwide. - Shippey, Karla C. (World Trade Press, 2008)
Do you or your company possess copyrights, brands, patents, trademarks, designs, or other related rights? If so, you have great opportunities in the new global marketplace, but you are also at great risk. A Short Course in International Intellectual Prope.